Brussels Bound: Policy Experience and Candidate Selection in European Elections. (September 2015) - Pemstein, Daniel; Meserve, Stephen A.; Bernhard, William T.
Parties in list systems must select candidates to best accomplish their electoral, organizational, and policy goals. In particular, parties must balance nominees' policy-making potential against other aspects of candidate quality, such as electoral viability. We exploit the unique variation in candidates and parties in European elections to study this trade-off. We develop a statistical ranking model to examine how parties facing varying strategic contexts construct electoral lists and apply it to a novel data set chronicling the political backgrounds of candidates in the 2009 European parliamentary elections. Parties that place high salience on the target legislature, are well positioned to influence policy once in office, and have less access to competing policy-making venues place particular emphasis on institution-specific policy-making experience relative to other types of candidate experience. This systematic variation in parties' candidate nomination strategies may fundamentally alter legislative output and partisan policy influence.